The role of tumor microenvironment reprogramming in primary liver cancer chemotherapy resistance - Zhao, Chunyu; Liu, Shanshuo; Gao, Feng; Zou, Yawen; Ren, Zhigang; Yu, Zujiang (Frontiers in Oncology, 2022)
Primary liver cancer (PLC) including hepatocellular carcinoma (HCC), intrahepatic cholangiocarcinoma (ICC), and other rare tumors is the second leading cause of cancer-related mortality and has been a major contributor to the cancer burden worldwide. Of all primary liver cancer, HCC is the most common type. Over the past few decades, chemotherapy, immunotherapy and other therapies have been identified as useful to the treatment of HCC. However, emerging evidence suggests that chemotherapy resistance is associated with higher mortality rates in liver cancer. Tumor microenvironment (TME) which includes molecular, cellular, extracellular matrix(ECM), and vascular signaling pathways is a complex ecosystem. It is now increasingly recognized that the tumor microenvironment plays a pivotal role in PLC prognosis, progression and treatment response. Cancer cells reprogram the tumor microenvironment to develop resistance to chemotherapy drugs which is distinct from normal differentiated tissues. Chemotherapy resistance mechanisms have been shown to be reshaped during TME reprogramming. For this reason, TME reprogramming can provide a powerful tool to better understand both cancer-fate processes and regenerative, with a potential to develop new treatment. In this review, we discusses the recent progress of tumor drug resistance, particularly tumor microenvironment reprogramming in tumor chemotherapy resistance, and focuses on its potential application prospects.